2005
DOI: 10.1016/j.cardiores.2005.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous integrin αβ and glycoprotein IIb/IIIa inhibition causes reduction in infarct size in a model of acute coronary thrombosis and primary angioplasty

Abstract: Simultaneous inhibition of IIb/IIIa and alpha(v)beta(3) causes a marked reduction in infarct size in a model of acute coronary thrombosis and primary PTCA that is associated with reduced myocardial microthrombi and inflammation, as well as improved myocardial blood flow and regional function. These results may have important implications in the treatment of acute coronary syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…In a model of acute coronary thrombosis and primary PCI, Sakuma and coworkers found that simultaneous inhibition of GP IIb-IIIa and integrin avb3 causes a marked reduction in infarct size that is associated with reduced myocardial micro-thrombi and inflammation, as well as improved myocardial blood flow and regional function [127].…”
Section: Off-target Effectsmentioning
confidence: 98%
“…In a model of acute coronary thrombosis and primary PCI, Sakuma and coworkers found that simultaneous inhibition of GP IIb-IIIa and integrin avb3 causes a marked reduction in infarct size that is associated with reduced myocardial micro-thrombi and inflammation, as well as improved myocardial blood flow and regional function [127].…”
Section: Off-target Effectsmentioning
confidence: 98%
“…To detect thrombi formed at the culprit lesion, radiolabeled fibrinogen, and antibodies against fibrin and plasminogen activator have been developed. Among them, several animal studies used 99m Tc-labeled platelet glycoprotein IIb/IIIa receptor agonist to detect thrombi [26,27].…”
Section: Nuclear Imaging Of Other Biological Processes Associated Witmentioning
confidence: 99%
“…Sakuma et al [38] compared the effect of the combined blockade of the GP IIb/IIIa receptor and integrin avb3 with the blockade of GP IIb/IIIa receptor alone, using a highly specific inhibitor -tirofiban, relating the results to a control group receiving saline. They found that out of these 3, simultaneous inhibition of GP IIb/IIIa and integrin avb3 cause a marked reduction in infarct size, in a model of acute coronary thrombosis and primary PCI, which is associated with reduced myocardial microthrombi and inflammation, as well as improved myocardial blood flow and regional function [38].…”
Section: Abciximabmentioning
confidence: 99%
“…They found that out of these 3, simultaneous inhibition of GP IIb/IIIa and integrin avb3 cause a marked reduction in infarct size, in a model of acute coronary thrombosis and primary PCI, which is associated with reduced myocardial microthrombi and inflammation, as well as improved myocardial blood flow and regional function [38]. Abciximab was not used in the study, but as far as we know, abciximab inhibits both -the GP IIb/IIIa receptor and integrin avb3, so we may assume that the effect would be similar.…”
Section: Abciximabmentioning
confidence: 99%